The Hidden Dimension: Context‐Dependent Expression of Repeatable Behavior in Copepods. (29th March 2020) - Heuschele, Jan; Lode, Torben; Andersen, Tom; Titelman, Josefin
Abstract: In ecotoxicology and aquatic ecology, we often ignore responses of individuals and focus on average responses. However, both terrestrial and aquatic animals display consistent behavioral differences between individuals. The distribution of behavioral differences within a population contains vital information for predicting population responses to novel environmental challenges. Currently, individual data for behavioral and physiological traits of small marine invertebrates are few, partly because such variation is lost within published group means and assumed normality. We tested the combined effects of an inorganic contaminant (copper) and a biological stressor (i.e., chemical cues of a fish predator) on activity in a marine copepod. Although direct stress effects were weak, individuals behaved consistently differently, depending on the context. Individual differences in behavior were only expressed under the influence of kairomones, but not by copper exposure alone. This finding indicates that copepods express repeatable and context‐dependent behavior. We also demonstrate how large variations in behavioral data can hide consistent differences between individuals. Environ Toxicol Chem 2020;39:1017–1026. © 2020 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals, Inc. on behalf of SETAC.